Pengaruh Kecepatan Pengadukan dan Penambahan Persentase Magnesium terhadap Kekerasan dan Laju Aus Komposit Matrik Logam dengan Metode Stir Casting - Arman Arman (Politeknik Negeri Ujung Pandang, 2010)
The cahracteristic of MMCs with stir casting method are influenced by speed of the stirrer, temperature process, percentage of magnesium and volume fraction. This research is stressed on the effect speed of stirrer and percentage of magnesium to characteristic of MMCs (Al/Al2O3) as a product of stir casting process. Materials used in this research are powder (Al2O3), Aluminium ingot and Al-31,3% Mg ingot as wetting agent, and Argon as gas of inert. The parameters used in MMCs manufacturing are stir casting with speed of stirrer 520 and 1510 rpm, at temperature 550°C and percentage of magnesium of 2, 5, 8, 10, 15% wt (material balance process). From this research result is obtained that high of speed stirrer and held up of magnesium will improve characteristic from metal matrix composite. At this research is obtained by speed of stirrer 1510 rpm and 15% Mg have composite optimum characteristic of hardness 98 HBN and wear resistance 3,59 × 10-6/mm3/mm of 1510 rpm and 10% Mg.